2003
DOI: 10.1002/mrd.10283
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of polo‐like kinase‐1 in rat oocytes and early embryos implies its functional roles in the regulation of meiotic maturation, fertilization, and cleavage

Abstract: Polo-like kinase 1 (Plk1) is a family of serine/threonine protein kinases that play important regulatory roles during mitotic cell cycle progression. In this study, Plk1 expression, subcellular localization, and possible functions during rat oocyte meiotic maturation, fertilization, and embryonic cleavages were studied by using RT-PCR, Western blot, confocal microscopy, drug-treatments, and antibody microinjection. Both the mRNA and protein of this kinase were detected in rat maturing oocytes and developing em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 44 publications
3
21
0
Order By: Relevance
“…The polo-like kinases (PLK1 and PLK3) provide important regulation of the G2/ M phase transition [55]. PLK1 is required for correct spindle function during mitosis and meiosis [56][57][58][59]. Both PLK mRNAs were expressed as maternal transcripts and continued to be expressed throughout development.…”
Section: Expression Of Genes Encoding Cell Cycle Control Genesmentioning
confidence: 99%
“…The polo-like kinases (PLK1 and PLK3) provide important regulation of the G2/ M phase transition [55]. PLK1 is required for correct spindle function during mitosis and meiosis [56][57][58][59]. Both PLK mRNAs were expressed as maternal transcripts and continued to be expressed throughout development.…”
Section: Expression Of Genes Encoding Cell Cycle Control Genesmentioning
confidence: 99%
“…[20][21][22] In meiosis, our earlier findings have indicated that Plk1 plays pivotal roles in regulating the microtubule assembly and spindle formation in mouse, rat and porcine oocytes. [23][24][25] Since both MEK1/2 and Plk1 are shown to localize to the spindle poles and play an essential role in spindle assembly during mouse oocyte meiotic maturation, we hypothesized that Plk1 might be a molecule interacting with MEK1/2 in the regulation of spindle formation.…”
Section: Introductionmentioning
confidence: 99%
“…The result indicated that ERK1/2 activities were required for MII arrest, but its loss was not sufficient for a full parthenogenetic activation. It has been previously reported that a large portion of in vitro cultured rat oocytes did not arrest at MII and developed to MIII (Fan et al, 2003b). Therefore, it will be interesting to check if ERK1/2 were inactivated in these rat oocytes.…”
Section: Discussionmentioning
confidence: 97%